Pengaruh Pemberian Ekstrak Kulit Batang Ailanthus altissima terhadap Perubahan Sel Hati dan Ginjal Mencit - Praptiwi, Praptiwi; Kuncari, Emma Sri; Agungpriyono, Dewi Ratih; Chairunnisa, Chairunnisa (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
The aim of this study was to determine the toxicopathological effect of Ailanthus altissima extract in liver and kidney of the mouse. The treatments in this study were: (1) negative control (carboxy methocellulose), extracts with concentration of (2) 1 mg/kg BW, (3) 10 mg/kg BW, (4) 100 mg/kg BW, and (5) 1000 mg/kg BW. Every treatment consisted of 5 mice. After receiving A.altissima extract for seven day consecutively, the mice were then euthanized with overdose of ether. The liver and kidney were taken and then fixed within 10% solution of Buffer Neutral Formalin (BNF). Histopathology slides of liver and kidney were processed and stained with Hematoxylline Eosin. The cell degeneration and cell death were observed with video photo microscope. The lesion of cell death and degeneration of hepatocytes and epithelium of kidney proximal tubule were counted. The data were analyzed statistically with ANOVA test continued with Duncan test. The result showed that cell necrosis of hepatocytes was not significantly different (P>0.05) compared to control treatment, while cell necrosis was increasing in the treatment of â‰¥ 10 mg/kg BW in tubuli of the kidney.